Plant Growing and Animal Husbandry of Kuzbass in the Late XIX - Early XX Centuries - V. G. Dorokhov; A. Yu. Karpinets; A. E. Pyanov (Научный диалог)
The article is devoted to the characterization of some problems of crop production and animal husbandry in the Kuzbass region (Kuzbass) during the late XIX - early XX centuries. The issues of livestock breeding dynamics in this territory are considered. Attention is paid to the characteristics of the structure of the Kuzbass herd in the indicated period. Based on the analysis of statistical data, the volumes of the Kuzbass herd in cabinet and state-owned villages of the Kuzbass region are presented. The question is raised about the characteristics of the agricultural districts of the Kuzbass region. The model farm of Kuzbass is being reconstructed at the time of 1913. The novelty of the study is that for the first time based on the processing of statistics, the state and dynamics of crop production and animal husbandry in the Kuzbass region (Kuzbass) in the late XIX - early XX centuries are presented. The relevance of the study is due to its scientific and social significance. The first is determined by the fact that this kind of research, based on the analysis of statistical data, is undertaken for the first time. The second is connected with the need to draw attention to the problems of sustainable socio-economic development of rural territories at present. The authors conclude that the degree of development of a particular agricultural sector in the region was determined by factors of a natural-geographical and climatic nature, as well as household needs.